NMR shielding and a thermodynamic study of the effect of environmental exposure to petrochemical solvent on DPPC, an important component of lung surfactant - Monajjemi, M.; Afsharnezhad, S.; Jaafari, M. R.; Abdolahi, T.; Nikosade, A.; Monajemi, H. (Russian Journal of Physical Chemistry, 2007)
The chemical and petrochemical industries are the major air polluters. Millions of workers are exposed to toxic chemicals on the job, and it is becoming more toxic, causing much damage to respiratory system, today. One of the main components of lung alveoli is a surfactant. DPPC (Dipalmitolphosphatidylcholine) is the predominant lipid component in the lung surfactant, which is responsible for lowering surface tension in alveoli. In this article, we used an approximate model and ab initio computations to describe interactions between DPPC and some chemical solvents, such as benzene, toluene, heptane, acetone, chloroform, ether, and ethanol, which cause lung injuries and lead to respiratory distress such as ARDS. The effect of these solvents on the conformation and disordering of the DPPC head group was investigated by calculations at the Hatree-Fock level using the 6--31G basis set with the Onsager continuum solvation, GAIO, and frequency models. The simulation model was confirmed by accurate NMR measurements as concerns conformational energy. Water can be the most suitable solvent for DPPC. Furthermore, this study shows that ethanol has the most destructive effect on the conformation and lipid disorder of the DPPC head group of the lung surfactant in our model. Our finding will be useful for detecting the dysfunction of DPPC in the lung surfactant caused by acute or chronic exposures to air toxics from petrochemical organic solvent emission source and chronic alcohol consumption, which may lead to ARDS.